2018
DOI: 10.4172/clinical-practice.1000408
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of appropriate medication- use by 2015 Beers criteria among elderly critically ill patients in Jordan.

Abstract: Background: Inappropriate prescribing can cause significant morbidity and mortality in geriatric patients. Studies implementing the updated 2015 American Geriatrics Society (ACG) Beers Criteria in the identification of potentially inappropriate medications (PIM) are lacking. In addition, there is limited information regarding PIM use in critically ill older adults.Objective: To investigate the prevalence, patterns and determinants of PIM among elderly critically ill patients in Jordan.Setting: critical care un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
0
2
1
1
Order By: Relevance
“…Similarly, at least one PIM use was noted in 98.2% of the ICU patients aged ≥60 according to 2012 Beers Criteria in a retrospective Brazilian study, and in more than 80% of the patients at ICU admission in another study by Floroff et al 20,21 PIM prevalence was 49.8% and 21.8%, respectively, according to the EU(7)‐PIM List and 2015 Beers Criteria in a retrospective study conducted in India with elderly in the ICU and internal medicine service, 22 where the prevalence as determined by the Beers Criteria was considerably lower than our results while EU(7)‐PIM List results were similar. At least one PIM, as identified by the 2015 Beers Criteria, was noted in approximately 33% of elderly patients hospitalized in the ICU of the university hospital in Jordan, 23 which was also considerably lower with respect to our results. Again, in another study conducted retrospectively in the ICU of a 3rd level hospital in China, one or more PIM was reported in 58.1% and 44.0% of the patients according to the 2015 Beers and STOPP/v2 Criteria, respectively 24 .…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…Similarly, at least one PIM use was noted in 98.2% of the ICU patients aged ≥60 according to 2012 Beers Criteria in a retrospective Brazilian study, and in more than 80% of the patients at ICU admission in another study by Floroff et al 20,21 PIM prevalence was 49.8% and 21.8%, respectively, according to the EU(7)‐PIM List and 2015 Beers Criteria in a retrospective study conducted in India with elderly in the ICU and internal medicine service, 22 where the prevalence as determined by the Beers Criteria was considerably lower than our results while EU(7)‐PIM List results were similar. At least one PIM, as identified by the 2015 Beers Criteria, was noted in approximately 33% of elderly patients hospitalized in the ICU of the university hospital in Jordan, 23 which was also considerably lower with respect to our results. Again, in another study conducted retrospectively in the ICU of a 3rd level hospital in China, one or more PIM was reported in 58.1% and 44.0% of the patients according to the 2015 Beers and STOPP/v2 Criteria, respectively 24 .…”
Section: Discussioncontrasting
confidence: 97%
“…Actually, the number of studies conducted with ICU patients are limited in other countries as well. In these studies, the prevalence of PIM was reported to be between 20–80% according to the 2012 and 2015 Beers Criteria, around 45% according to the STOPP/v2 Criteria, and around 50% according to the EU(7)‐PIM List 20‐24 . Considering all these issues, there is an apparent need for prospectively designed studies with elderly ICU patients in order to determine and compare the prevalence of PIM using the current Beers (2019) Criteria, STOPP/v2 Criteria and the EU(7)‐PIM List.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have indicated that cerebral toxoplasmosis is one of the major opportunistic infections that occurs in 5–40% of patients with AIDS (36, 37). However, a most recent study in Uganda has reported a case of primary cerebral toxoplasmosis in an HIV-negative individual adult; indicating that HIV/AIDS may not be a prerequisite for cerebral toxoplasmosis (38).…”
Section: Discussionmentioning
confidence: 99%
“…Hasil penelitian ini lebih rendah dari beberapa penelitian antara lain di di India 61,9% (Beers 2019) 21 , 45,75% (Beers 2019) 24 dan di Karawang 52,2% (Beers 2012) 15 . Namun pada penelitian lain kejadian PIMs didapatkan lebih rendah dibandingkan penelitian ini yaitu 33,1% (Beers 2015) 40 dan 34,8% (Beers 2012) 19 . Kejadian PIMs yang ditemukan dari beberapa penelitian persentasenya berbeda-beda, hal ini dapat disebabkan karena perbedaan tempat penelitian, jumlah sampel dan juga metode penelitian yang digunakan.…”
Section: Gambar 1 Proses Seleksi Rekam Medis Pasienunclassified